Increased Cognitive Load during Video Game Play Reduces Rape Myth Acceptance and Hostile Sexism after Exposure to Sexualized Female Avatars - Read, Glenna L.; Lynch, Teresa; Matthews, Nicholas L. (Sex roles, 2018)
The present study investigated how task demand (cognitive load and interactivity) and avatar sexualization in a video game influenced rape myth acceptance (RMA), hostile sexism, and self-objectification. In a between-subjects design, 300 U.S. college students either played or watched someone else play a videogame as either a sexualized or non-sexualized female avatar under high (memorize 7 symbols) or low (memorize 2 symbols) cognitive load. Hypotheses were derived from the limited capacity model of motivated mediated message processing (LC4MP) and perspectives on stereotype processing. Results contradicted hypotheses that greater task demands and sexualization would produce greater RMA, hostile sexism, and self-objectification. Instead, we found that sexualization did not affect these variables. Greater cognitive load reduced rape myth acceptance and hostile sexism for those in the sexualized avatar condition, but it did not affect self-objectification. We discuss these results with respect to the LC4MP and suggest that the processing of stereotype-inconsistent information might be the underlying cause of these unexpected findings. These results provide tentative evidence that cognitively demanding video game environments may prompt players to focus on stereotype-inconsistent, rather than stereotype-consistent, social information.